Pola Asuh Orang Tua Perspektif Mubadalah (Studi pada Keluarga K.H. Ahmad Siradjuddin) - Bhismoadi Tri Wahyu Faizal; Anis Amalia; Hosen; Maimun (Fakultas Syariah IAIN Madura, 2022)
This study Discusses the phenomenon of gender equality in the family scope. This is because a person's responsiveness or passiveness to gender issues is often influenced by the parenting style he received from childhood. So the planting of gender equality should be instilled from an early age in every family included in the kiai’s family.